Building Public Trust: The Future of Corporate Reporting - A.DiPiazza Samuel (Wiley, 2002)
Building Public Trust, by Samuel A. DiPiazza Jr. and Robert G. Eccles, couldn't be more timely or necessary. Arriving in the wake of a seemingly endless stream of corporate accounting scandals--which in a matter of months have bankrupted Enron and brought WorldCom and Global Crossing down to earth--this book offers a bona fide framework for a new, open form of transparent financial reporting that should prove more palatable to businesses and their stakeholders, and more effective than any of those in misuse today. DiPiazza, CEO of PricewaterhouseCoopers, and Eccles, president of Advisory Capital Partners, certainly know of which they speak, and they lay out a highly informed and quite feasible system that actively involves every member of the so-called corporate reporting supply chain: executives, boards of directors, independent auditors, information distributors, third-party analysts, investors, and various other stakeholders. They propose specific ways to develop three key elements (a spirit of transparency, a culture of accountability, and people of integrity) that work together to "create public trust in markets." Based on their extensive firsthand experiences, they further show how using these principles can lead to a scenario where "capital is being allocated more efficiently all over the world." The timeliness of this book is one thing, the content within its pages another, and on both counts Building Public Trust definitely delivers. --Howard Rothman